Electrochemical Synthesis of Nanoparticles of Zinc Oxide Using Film Former MHB 3000 P2e - Smitiukh, O.V.; Yanchuk О.М.; Marchuk О.V.; Khmaruk, Ju.O.; Yatsyshyn, M.M.; Vyshnevskyi, O.A.; Velymchanitsa, I.I. (Physics and Chemistry of Solid State, 2025)
In this work, we present the electrochemical synthesis of zinc oxide in the presence of film former MHB 3000 P2e from a sodium chloride solution and the corresponding concentration of MHB 3000 P2e (in the range of 0 to 0.35 g/L). For all 10 samples X-ray analysis has been carried out and synthesized samples are one-phase. A unit cell of the crystalline structure of the nanoparticles is described as the hexagonal crystal system (Space Group P63mc) and is non-centrosymmetric. The second coordination environment of the crystal system contains three zinc atoms located in tetrahedral positions, which accounts for 3/8 of all tetrahedral voids. The octahedral voids are empty, allowing for doping with such substances as transition metal atoms with a tetrahedral environment, and are characterized by small atomic radii (e.g., iron, nickel, cobalt). The obtained nanoparticles were also analyzed using SEM. From the obtained images, information regarding the width, length, and thickness of the particles was gathered. It is important to note that the width and length of the particles are quite significant; however, the thickness of the particles ranges from 25 to 25.7 nm. Thus, at low film former concentrations, particle parameters are smaller, while with increasing film former concentration, both thickness and length significantly increase.